2020
DOI: 10.3390/sports8020019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Duration and Intensity of the World’s Top-Level Badminton Matches: A Consideration of the Increased Acute Injuries among Elite Women’s Singles Players

Abstract: The purpose of this study was to clarify whether there have been any specific changes in the characteristics of the world's top-level women's singles badminton matches compared to men's singles matches after the current badminton scoring system was implemented in 2006. We compared the characteristics of the matches between the Super Series tournaments in 2007 and 2017. Match duration increased as the rally and rest times increased in both men's and women's singles matches. Specifically, in women's singles, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, newer quantifications have adjudged this figure to be in excess of 94% [ 10 ]. Accordingly, the applicability of antecedent research to contemporary performance may be limited, and without procuring specific knowledge of the current physiological demands, training regimens are likely outdated and ineffective [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, newer quantifications have adjudged this figure to be in excess of 94% [ 10 ]. Accordingly, the applicability of antecedent research to contemporary performance may be limited, and without procuring specific knowledge of the current physiological demands, training regimens are likely outdated and ineffective [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of these studies showed that the scaling of equipment and playing area improve the players’ match performance, engagement, enjoyment and the development of desirable movement patterns related to motor variability. However, in badminton, the research has focused to analyze the following aspects: technical and tactical [ 30 ], physiological [ 31 , 32 ] or performance analysis [ 33 , 34 , 35 , 36 ] in elite and junior elite players, and not so much in scaling the equipment and play space for junior players. Although, some associations and federations, such as the Spanish Badminton Federation [ 37 ], in a similar way to the tennis 10’s program developed by the International Tennis Federation, do structure badminton competitions for junior players, to manipulate key task constraints.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, six out of eight participants were doubles players. As the physical demands of singles and doubles disciplines in badminton differ from each other [ 31 , 32 , 33 , 34 ], the extent to which HRV indices reflect changes in the players’ fatigue status may be different between singles and doubles players. Second, we could not evaluate the players’ overall daily training load since we could not monitor the training intensity during their resistance training sessions by measuring HR.…”
Section: Discussionmentioning
confidence: 99%